Prevalence and characterization of verotoxigenic-Escherichia coli isolates from pigs in Malaysia - Ho, Wing Sze (BioMed Central, 2013)
BACKGROUND: Postweaning diarrhea caused by pathogenic Escherichia coli, in particular verotoxigenic E. coli (VTEC), has caused significant economic losses in the pig farming industry worldwide. However, there is limited information on VTEC in Malaysia. The objective of this study was to characterize pathogenic E. coli isolated from post-weaning piglets and growers with respect to their antibiograms, carriage of extended-spectrum beta-lactamases, pathotypes, production of hemolysins and fimbrial adhesins, serotypes, and genotypes. RESULTS: PCR detection of virulence factors associated with different E. coli pathotypes (ETEC, EPEC, EHEC, and VTEC) revealed that VTEC was the only pathotype identified from six swine farms located at north-western Peninsular Malaysia. A low prevalence rate of VTEC was found among the swine samples (n = 7/345) and all 7 VTEC isolates were multidrug resistant. Five of these isolates from different hosts raised in the same pen were likely to be of the same clone as they shared identical sero-pathotypes (O139:H1, VT2e/α-hly/F18), resistance profiles and DNA fingerprinting profiles. Two other serotypes, O130: H26 (n = 1) and O168: H21 (n = 1) carrying virulence factors were also identified. O168: H21 is possibly a new serotype as this has not been previously reported. CONCLUSIONS: The occurrence of VTEC with infrequently encountered serotypes that are multidrug resistant and harbouring virulence factors may be of public health concern. The detection of possible clones in this study also showed that the combination of different typing tools including phenotyping and genotyping methods is useful for molecular epidemiologic surveillance and studies.